Multi-Temporal Chlorophyll-A Monitoring in Lake Matano and Towuti Using Landsat 8 OLI Imagery - Lalu Muhamad Jaelani; Rossita Yuli Ratnaningsih (Journal of Applied Geospatial Information, 2019)
Lake Matano and Towuti are two of 15 lake priorities in Indonesia. For preservation purposes, a routine water quality monitoring from satellite is needed. In this study, 11 scenes of Landsat 8 data were processed to produce chlorophyll-a concentration as an indicator of water quality condition on these two lakes. The result showed that water quality in Lake Matano and Towuti were in low cholorphyll-a condition with chlorophyll-a concentration ranged from 0.000– 2.298 mg/m3, 0.000-2.236 mg/m3, respectively. The accuracy of estimated Chlorophyll-a in these two lakes were affected by an inaccurate of atmospheric corrected data. To improve the accuracy, a more accurate atmospheric correction algorithm for Landsat 8 was still required.